A Risk Terrain Model of Residential Burglaries in Valdosta, Georgia - Varney, Kristen E. (My University, 2016)
Crime has four aspects: an offender, a victim, a law that is broken, and a place where the crime occurs (Brantingham & Brantingham, 1991). This research will look at this fourth aspect to determine what environmental features, if any, affect residential burglaries. It's not about why people commit burglaries, but why offenders choose the targets they do. Rather than focusing on the biological or social reasoning behind an individual's criminal behavior, environmental criminology instead focuses on the locations in which crime occurs. The goal is to find significant patterns in crime locations and look for environmental features that may help explain the increased criminogenic activity. In this particular research, which utilizes a process called Risk Terrain Modeling to assess burglaries in Valdosta, Georgia, these identified environmental risk features are weighted and a map of places at risk for burglary is created that can then aid police officers and city planners in allocating resources in a cost-efficient manner and possibly developing preventative measures.
Chapter I: INTRODUCTION 1 Surveys of Burglars 2 Risk Terrain Modeling 5 Chapter II: LITERATURE REVIEW 8 Identifying Risk Factors from Previous RTM Studies 9 Weighting Risk Models 10 Chapter III: METHODOLOGY 13 Chapter IV: RESULTS 16 Modeling Burglaries in Valdosta 16 Testing the Model 21 Chapter V: DISCUSSION AND CONCLUSION 25 REFERENCES 28 APPENDIX A: Institutional Review Board Exemption 32
Keywords: Mobile geographic information systems; Risk Terrain Modeling; Risk assessment; Crime--Analysis; Criminal justice, Administration of--United States--Georgia; Criminology; Burglary